“I am not afraid to try this food!” determinants of tourists' risk acceptance, willingness-to-try and insights for enhancing food tourism strategies in Perhentian, Terengganu, Malaysia / Wan Hafiz Wan-Zainal-Shukri ... [et al.] - Wan-Zainal-Shukri, Wan Hafiz; Jaafar, Siti Nur’Afifah; Ismail, Fathilah; Nik Ubaidillah, Nik Hafizah (Universiti Teknologi MARA, Terengganu, 2024)
Food consumption plays a crucial role in the tourism experience, yet understanding the factors that influence tourists' willingness to try (WTT) unfamiliar local foods remains limited. This study addresses this gap by examining the interplay of financial, environmental, health, and service-related factors that impact tourists' decisions to engage with local cuisine. The problem lies in the limited exploration of how various risks and motivators affect WTT, particularly in emerging markets like Malaysia. While previous research has focused on food safety and cultural experience, the role of servicescape, self-motivation, and information-seeking behaviour is underexplored. This research utilized a qualitative methodology, employing semi-structured interviews combined with photo-elicitation to capture in-depth insights from European tourists at Perhentian Island, Terengganu. The study aims to identify the primary factors influencing WTT and how potential risks can be leveraged by restaurants, tour operators, and local authorities to enhance the food tourism experience. Data was gathered from 20 European participants, with discussions revolving around their risk concerns, trust issues, memorable experiences, and curiosity about local food. The findings revealed that financial affordability, environmental sustainability, health risk, trust in food safety, and positive service encounters significantly influence WTT. Self-motivation, online reviews, and positive service encounters also emerged as critical drivers for exploring unfamiliar foods. The research contributes to the existing literature by filling the gap in understanding the dynamic role of environment, service encounters, and trust in their dining experience. The study’s contributions highlight the importance of promoting food safety, environmental sustainability, and positive service experiences in boosting food tourism. This research provides actionable insights for restaurants, tour operators, and local authorities to improve food tourism strategies, ultimately fostering economic growth in the tourism sector.